2018
DOI: 10.3390/nu10010036
|View full text |Cite
|
Sign up to set email alerts
|

Potential Anticancer Properties of Osthol: A Comprehensive Mechanistic Review

Abstract: Cancer is caused by uncontrolled cell proliferation which has the potential to occur in different tissues and spread into surrounding and distant tissues. Despite the current advances in the field of anticancer agents, rapidly developing resistance against different chemotherapeutic drugs and significantly higher off-target effects cause millions of deaths every year. Osthol is a natural coumarin isolated from Apiaceaous plants which has demonstrated several pharmacological effects, such as antineoplastic, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 90 publications
0
45
0
Order By: Relevance
“…For the next 6 weeks, in ethanol group, rats had an ethanol‐containing Lieber‐DeCarli liquid diet, containing 8% (w/v) ethanol (36% of daily calories) . The rats in the ethanol + osthole group had the same ethanol diet but were co‐treated with osthole (100 mg/kg/d) by intraperitoneal injection, and the rats in control group had the normal Lieber‐DeCarli liquid diet without ethanol (the ethanol was displaced by maltodextrin, with the same amount of calories). All rats were free access to the diets which were refreshed every day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the next 6 weeks, in ethanol group, rats had an ethanol‐containing Lieber‐DeCarli liquid diet, containing 8% (w/v) ethanol (36% of daily calories) . The rats in the ethanol + osthole group had the same ethanol diet but were co‐treated with osthole (100 mg/kg/d) by intraperitoneal injection, and the rats in control group had the normal Lieber‐DeCarli liquid diet without ethanol (the ethanol was displaced by maltodextrin, with the same amount of calories). All rats were free access to the diets which were refreshed every day.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have found several herbs, and their monomers could ameliorate alcohol‐induced ONFH in animal models . Osthole, a coumarin bioactive derivative, obtained from many medical plants, is commonly used as ingredients in herbal medicine and functional foods . With the in‐depth investigations, osthole is revealed to possess a wide range of different pharmacological effects, including hepatoprotective, vasorelaxant, antileishmanial, neuroprotective, spasmolytic and antimicrobial properties .…”
Section: Introductionmentioning
confidence: 99%
“…Osthole is a natural coumarin present in the medicinal plant Cnidium monnieri. Because osthole demonstrates significant protective effects in animal models of hepatic diseases (30,31), cancer (54), diabetes (27,28), osteoarthritis (55), cardiovascular (56,57) and allergic diseases (18,34), it is a promising natural lead compound for drug discovery. Herein we demonstrate that osthole inhibits mast cell activation via MRGPRX2.…”
Section: Discussionmentioning
confidence: 99%
“…Osthole has shown great potential in the treatment of several disorders through their anti-inflammatory, anti-bacterial, and anti-allergic properties [29]. Previous studies have shown that osthole inhibits the proliferation of cancer via the suppression of neovascularization [24]. There are some similarities between corneal neovascularization and tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has potential therapeutic applications because of its significant and diverse pharmacological (anti-cancer, anti-osteoporotic, and anti-proliferative) activities[21-23]. Previous studies have demonstrated that osthole exerts anti-cancer activity by inhibiting angiogenesis, suggesting a potential role of osthole in anti-angiogenesis [24]. However, the role of osthole in corneal neovascularization is still unclear.…”
Section: Introductionmentioning
confidence: 99%